2022
DOI: 10.1371/journal.pone.0273806
|View full text |Cite
|
Sign up to set email alerts
|

Religious service attendance and mortality among older Black men

Abstract: Religious institutions have been responsive to the needs of Black men and other marginalized populations. Religious service attendance is a common practice that has been associated with stress management and extended longevity. The objective of this study was to examine the relationship between religious service attendance and all-cause mortality among Black men 50 years of age and older. Data for this study were from NHANES III (1988–1994). The analytic sample (n = 839) was restricted to participants at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Beyond allowing patients to feel heard and recognized as individuals, respecting and recognizing patients' spirituality has also been associated with better outcomes, such as improved quality of life (Balboni et al., 2010 ), as patients' beliefs are associated with decreased mortality (Bruce et al., 2022 ; Li et al., 2016 ). Conversely, not addressing spirituality and religion has been correlated with patient perception of poorer quality of life (Balboni et al., 2010 ; Vallurupalli et al., 2012 ), poorer quality of care, and lower satisfaction with care (Astrow et al., 2007 ).…”
Section: Incorporating the Interdisciplinary Team To Provide Spiritua...mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond allowing patients to feel heard and recognized as individuals, respecting and recognizing patients' spirituality has also been associated with better outcomes, such as improved quality of life (Balboni et al., 2010 ), as patients' beliefs are associated with decreased mortality (Bruce et al., 2022 ; Li et al., 2016 ). Conversely, not addressing spirituality and religion has been correlated with patient perception of poorer quality of life (Balboni et al., 2010 ; Vallurupalli et al., 2012 ), poorer quality of care, and lower satisfaction with care (Astrow et al., 2007 ).…”
Section: Incorporating the Interdisciplinary Team To Provide Spiritua...mentioning
confidence: 99%
“…While acknowledging the possible influence of covariates such as depression and smoking, the authors found that women who attended religious services more than once a week had 33% lower all‐cause mortality risk compared to those who never attended (Li et al., 2016 ). Another compelling example is from research on Black men in the United States, a historically burdened and marginalized group with shorter life expectancy compared to other demographic groups, which identified that more frequent participation in religious services had a 47% reduction in all‐cause mortality compared to peers without such involvement (Bruce et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…One's religiosity may also be a potent variable (with mixed negative and positive associations) in diseases related to mortality, such as cancer (e.g., Almaraz et al, 2022;Elkhalloufi et al, 2022;Fradelos et al, 2018;Kugbey et al, 2020;Moorman et al, 2019;Thun e-Boyle et al, 2006;Thygesen et al, 2012;Van Ness et al, 2003) and cardiovascular disease (Brewer et al, 2022;Elhag et al, 2022;Seybold & Hill, 2001;Svensson et al, 2020). Factors associated with religiosity that may negatively affect mortality include delaying diagnosis of cancer (Moorman et al, 2019) and a reliance on an external locus of control (believing God controls health; Kinney et al, 2002), whereas the context of religious service attendance may have a positive effect on mortality (Bruce et al, 2022) Relatedly, one religious practice, fasting during Ramadan, has been shown to improve some aspects of the cardiovascular system (lipid profile, oxidative stress; Ahmed et al, 2022;Al-Shafei, 2014;Naz et al, 2022), although fasting is not recommended for all individuals due to some health concerns (Malinowski et al, 2019). Additionally, Stavrova (2015) and Ebert et al (2020) noted that any health and mortality benefits of religiosity across religions and cultures are limited to regions where religiosity is considered common and socially desirable; therefore, when considering the effects of reli-giosity on aspects of health, one should consider the acceptance of practices in their living context.…”
Section: The Intersection Of Religion Spirituality and Healthmentioning
confidence: 99%